THE USE OF CONTEXTUAL VIDEO TO IMPROVE STUDENTS' LISTENING ABILITY : A quasi experimental study of eighth year students in one of state junior high schools in Bandung - Kamilah, Mardiya (2013)
ABSTRACT This study, entitled "The Use of Contextual Video to Improve Student' Listening ability" aimed to investigate the effectiveness of contextual video usage in improving the students' listening ability and to find out the students' responses toward the use of contextual video in listening practice related to the students' English knowledge and the students' psychology. The participants of this study were the students of eighth year in one junior high school in Bandung that were designed into two groups: experimental class and control class. This study revealed that, in average, the experimental class (M =79.45, SE=1.69, p<0.05) is significantly different from the control class (M=73.21, SE=1.96) in listening with the effect size of 0.27. Thus it can be assumed that contextual video is effective in improving students' listening ability. Furthermore, the result of students' responses on questionnaire analysis indicated that the students' responses toward the use of contextual video in listening practice were positive. Most of them stated that contextual video gave more advantages than the disadvantages. Related to the students' English knowledge, most students stated that contextual video helped them in understanding the meanings and the messages that were conveyed in the conversation. Furthermore, related to the students' psychology, most students stated that contextual video helped them to keep focused and concentrated during listening practice. In conclusion, it was found that contextual video can be used as an alternative teaching medium in teaching listening or the other language skills. For consideration, contextual video can also be used in other topics or even subjects. ABSTRAK Penelitian yang berjudul "Penggunaan Kontekstual Video Untuk Meningkatkan Kemampuan Listening Siswa" ini bertujuan untuk menganalisis dan mencari tahu mengenai keefektifan dari penggunaan kontekstual video dalam pembelajaran listening dan juga mencari tahu bagaimana respon dari siswa terhadap penggunaan kontektual video dalam pembelajaran listening terkait dengan aspek pengetahuan siswa tentang bahasa Inggris dan aspek psikologis siswa itu sendiri dalam belajar. Partisipan dari penelitian ini adalah siswa kelas delapan SMP negeri 40 kota Bandung yang dikelompokan kedalam dua kelas: yang pertama adalah kelas 8A sebagai kelas control dan yang kedua adalah kelas 8D sebagai kelas eksperimental (placebo). Hasil dari penelitin menunjukan bahwa kontextual video efektif digunakan dalam pembelajaran listening. Hal trsebut ditunjukan oleh rata-rata nilai siswa di kelas experimental (=79.45, SE=1.69, p<0.05) yang dengan signifikan lebih tinggi dari rata-rata nilai siswa di keas control (M=73.21, SE=1.96) pada test akhir setelah pemberian treatment selesai dilakukan. Selain itu, hasil penelitian juga menunjukan bahwa respon yang diberikan oleh siswa terhadap penggunaan kontextual video dalam pembelajaran listening sangat baik. Terkait dengan aspek pengetahuan bahasa Inggris, sebagian besar siswa berpendapat bahwa kontekstual video dapat membantu mereka meningkatkan kemampuan dalam mendengarkan pelafalan dari setiap kosa kata bahasa Inggris yang disebutkan dalam kontektual video dan juga menambah pengetahuan mereka mengenai penggunaan kosa-kata tertentu dalam situasi tertentu. Terkait dengan aspek pisikologis siswa, para siswa juga sependapat jika kontektual video dapat membuat mereka lebih semangat, termotivasi, lebih ingin tahu dan lebih mengerti juga dapat lebih focus selama proses pembelajaran berlangsung. Selebihnya, Kontektual video tidak hanya cocok digunakan dalam pembelajaran listening tapi juga cocok di terapkan sebagai salah satu media mengajar untuk subjek pelajaran lainnya.